Control interno como mecanismo de gestión en la Bananera Dos Hermanos del cantón Simón Bolívar período 2021 - Molina Goyes, Joselin Lisbeth (2023)
Internal control stands out as a crucial management mechanism at Bananera Dos Hermanos during the 2021 period in Cantón Simón Bolívar. This study evaluated how the implementation of sound internal control influenced efficiency and compliance with financial and operational standards. This study reveals that the company has maintained accounting policies aligned with international regulations, such as IAS 8, demonstrating a commitment to transparency and accuracy in financial reporting. However, areas for improvement were detected in the documentation and robustness of accounting policies. The study also applied the COSO model to assess internal control weaknesses, identifying the lack of a defined control environment and poor risk assessment. These weaknesses could increase the levels of risk associated with cost management and decision making. Internal control emerges as a vital tool to ensure regulatory compliance and improve operational efficiency at Bananera Dos Hermanos during the 2021 period, but additional efforts are required to strengthen its implementation and mitigate risks